Respuesta :
I don't know if it's (1/x )+ 5 or 1/(x+5) anyways
g(x) = x-2 so in f(g(x)) you replace every x with x-2
f(g(x)) = (1/(x-2)) + 5 or 1/(x-2-5) = 1/(x-7)
if the function is like the first form so you avoid numbers which will make your denominator equals zero
x-2 = 0, x=2 or x-7 = 0, x=7
so if it's like first one answer is R - 2
if it's second answer is R - 7
g(x) = x-2 so in f(g(x)) you replace every x with x-2
f(g(x)) = (1/(x-2)) + 5 or 1/(x-2-5) = 1/(x-7)
if the function is like the first form so you avoid numbers which will make your denominator equals zero
x-2 = 0, x=2 or x-7 = 0, x=7
so if it's like first one answer is R - 2
if it's second answer is R - 7